Caries in orphan children: prevalence and determinants-a systematic review and meta-analysis - Ayat Gamal-AbdelNaser; Mennat Allah Ashraf A.Elsabour; Nagwa Mohamed Ali Khattab (BMC, 2024)
Abstract Background Orphan children represent a category of children who lost their family support. Their health status is poorer when compared to their parented counterparts. As the most prevalent disease in the world, dental caries is expected to affect orphans greatly. Being vulnerable, health status of orphan children must be monitored and studied; so that health improvement plans would be formulated. Therefore, this systematic review focuses on the extent of the dental caries problem among institutionalized orphan children and its determinants. Methods The review has two outcomes: comparing caries experience of institutionalized children to their parented counterparts, and reviewing the determinants of caries in the exposure group. Two systematic searches (one for each outcome) were run on MedLine via PubMed, Cochrane library, LILACS, Egyptian knowledge bank (EKB) and Google Scholar; beside hand search and searching grey literature. Results The searches yielded 17,760, followed by 16,242 records for the first and second outcomes respectively. The full text was screened for 33 and 103 records for the two outcomes respectively; after translating non-English reports. Finally, the review included 9 records to address the first outcome and 21 records for the second. The pooled results showed that the exposure group may show slightly poorer caries experience regarding permanent teeth (pooled mean difference of DMF = 0.09 (-0.36, 0.55)); but they have a much poorer caries experience regarding primary teeth health (pooled mean difference of dmf = (0.64 (-0.74, 2.01)). Meta-analysis of the caries determinants showed that institutionalization increases the risk of caries by 19%. Gender showed slight effect on caries risk with males being more affected; while primary teeth revealed higher risk of caries when compared to permanent teeth. Conclusion Limited by the heterogeneity and risk of bias of the included studies, meta-analyses concluded that institutionalized orphan children have higher risk of caries. Yet, the institutionalization circumstances were not well-documented in all the included studies. So, the complete picture of the children's condition was not possibly sketched. Trial registration Protocol has been registered online on the PROSPERO database with an ID CRD42023443582 on 24/07/2023.